Smart antennas for wireless applications / Noor Shazana Idris - Idris, Noor Shazana (2006)
The aim of this thesis is to synthesize the radiation patterns and performance of the linear array antenna. The array antennas synthesis was done using the Woodward-Lawson and Dolph-Chebyshev. The results were carried out by varying different limiting parameters. This thesis presents the concept of smart antenna system by studying the performance of antenna array.